PENGEMBANGAN KARAKTER DAN KETERAMPILAN SISWA MELALUI KEGIATAN P5 DENGAN TEMA BAZAR “MAKANAN HASIL PERTANIAN” DI SMA NEGERI 3 TUBAN - Mochamad Deni Leo A.B, Mochamad Deni Leo A.B; Jazilatun Ni’mah, Jazilatun Ni’mah; Nur Alisa Rahmawati, Nur Alisa Rahmawati (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
This study aims to analyze the effectiveness of project activities to strengthen the profile of students Pancasila (P5) with the theme Bazaar “Food Agricultural Products” in developing the character and skills of students in SMA Negeri 3 Tuban. This activity is designed to provide hands-on learning experience (experiential learning) that integrates the values of Pancasila with entrepreneurial practices and utilization of local potential. The research method used is descriptive qualitative data collection through observation, interviews, and document analysis. The results showed that the activities of Bazaar P5 "Food Agricultural Products" managed to develop several aspects of student character, including independence, creativity, mutual cooperation, responsibility, and concern for the environment and local wisdom. In addition, students also demonstrate improvements in critical thinking, problem solving, communication, collaboration, and entrepreneurial skills. The implication of this study is the importance of the implementation of P5 as an innovative platform for the formation of a holistic Pancasila student profile and relevant to the challenges of the Times. Keywords: Characteristics And Skills Of Students, Through P5 Activities.